Tumor necrosis factor-alpha induces renal cyclooxygenase-2 expression in response to hypercalcemia - Battula, Sailaja (2012)
The effect of tumor necrosis factor-alpha (TNF) on cyclooxygenase-2 (COX-2) expression in the renal outer medulla (OM) was determined in a model of dihydrotachysterol (DHT)-induced hypercalcemia. Increases in serum calcium and water intake were observed during ingestion of a DHT-containing diet in both wild type (WT) and TNF deficient mice (TNF(−/−)). Polyuria and a decrease in body weight were observed in response to DHT treatment in WT and TNF(−/−) mice. A transient elevation in urinary TNF was observed in WT mice treated with DHT. Moreover, increased urinary levels of prostaglandin E(2) (PGE(2)) and a corresponding increase in COX-2 expression in the OM were observed in WT mice fed DHT. Increased COX-2 expression was not observed in TNF(−/−) mice fed DHT, and the characteristics of PGE(2) synthesis were distinct from those in WT mice. This study demonstrates that COX-2 expression in the OM, secondary to hypercalemia, is TNF-dependent.